Kinematic analysis of the women's javelin throw at the IAAF World Championships, Daegu 2011 - Jung, J. H.; Kim, D. S.; Kang, H. Y.; Chae, W. S.; Lim, Y. T.; Yoon, C. J.; Lee, H. S. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to analyze the kinematic variables for the women's javelin throw at the IAAF World Championships, Daegu 2011. Three-dimensional motion analyses of the eight players who qualified for the final round were carried out to obtain the data. The results showed that average release, attitude, and attack angles were 38.0±2.0°, 40.4±4.3°, and 3.7±1.1°, respectively. At the release, the average inclination angle of the trunk, upper arm, forearm were 60.8±8.3°, 47.3±10.1°, and 62.6±10.6°, respectively. Moreover, the release velocity and the release height results averaged 25.60±1.16 m/s and 1.86±0.05 m. The crossover phase and delivery phase had average distances of 1.88±0.31 m and 1.53±0.21 m. After release, the average distance between the landing foot and the foul line was 1.72±0.63 m.